Characteristics of growth and microcystin production of Microcystis aeruginosa exposed to low concentrations of naphthalene and phenanthrene under different pH values. (November 2019) - Huang, Yingping; Pan, Hongyu; Liu, Huigang; Xi, Ying; Ren, Dong
Abstract: Here, Microcystis aeruginosa ( M. aeruginosa ) was studied to analyze the effects of 0.5 mg L −1 naphthalene and 0.05 mg L −1 phenanthrene on profiles of cell growth, chlorophyll- a content and Microcystin-LR (MC-LR) production at different pH values. The results indicated that for both the naphthalene and phenanthrene treatments, the specific growth rates were higher in pH 10.0 than in either pH 7.0 or pH 5.0. In the presence of low concentrations of naphthalene or phenanthrene, chlorophyll- a in medium increased significantly more in pH 10.0 than pH 5.0. chlorophyll- a in cell was significantly lowered when exposed to naphthalene in both pH 10.0 and pH 7.0, and was higher when exposed to phenanthrene in pH 10.0 than pH 5.0. HPLC analysis revealed that the extracellular MC-LR concentrations in M. aeruginosa exposed to either naphthalene or phenanthrene were lower than in control M. aeruginosa at pH 5.0. The intracellular MC-LR levels in toxic M. aeruginosa cells exposed to naphthalene or phenanthrene were higher than in the controls at pH 10.0. Our study suggests that the MC-LR production of M. aeruginosa was affected by the pH value when low concentrations of either naphthalene or phenanthrene were present in the water. These results indicate that the pH value should not be ignored when evaluating the risk of chemicals that promote MC-LR production in eutrophic waters. Highlights: The growth of M. aeruginosa was affected by pH value in the presence of Polycyclic Aromatic Hydrocarbons. Chlorophyll- a in M. aeruginosa was affected by the pH value in the presence of Polycyclic Aromatic Hydrocarbons. MC-LR production of M. aeruginosa was affected by the pH value and Polycyclic Aromatic Hydrocarbons.